Effects of hydroethanolic garlic extract on oxidative stress, lipolysis, and glycogenesis in high-fat diet-fed Drosophila melanogaster - Ayodeji E. Adepoju; Monde Ntwasa; Sogolo L. Lebelo; Temitope A. Oyedepo; Ademola O. Ayeleso (Shahrekord University of Medical Sciences, 2024)
Introduction: Metabolic syndrome is multifaceted health condition associated with metabolism, which leads to the accumulation of oxidation products and impairment of the antioxidant system. Medicinal, edible plant alternatives are being sought to prevent the predisposing factors of metabolic syndrome, one of which is obesity. We studied the effects of hydroethanolic garlic extract (HGE) on oxidative stress, lipolysis, and glycogenesis in high-fat diet-fed Drosophila melanogaster. Methods: The HGE was processed and antioxidant assays (in vitro and in vivo) coupled with metabolic biomarkers were assayed following standard procedures. Results: HGE inhibited ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), hydroxyl, and hydrogen peroxide radicals in high-fat-fed D. melanogaster. The HGE also reduced the activity of superoxide dismutase and increased catalase activity significantly. The HGE promoted lipolysis and glycogenesis by reducing cholesterol, triglycerides, and total sugar concentrations while glycogen content was increased. Conclusion: Our results revealed that HGE improved the antioxidant defense system and promoted lipolysis and glycogenesis in metabolic deranged D. melanogaster. This suggests the therapeutic usefulness of garlic in the management of metabolic diseases.